Focal controlled drug delivery - Khan, Wahid; Domb, Abraham J. (Advances in Delivery Science and Technology, 2014)
The concept of Focal Drug Delivery has been applied for treating illnesses that are localized to a certain tissue or organ. These delivery systems are applied directly to the diseased site and deliver a desired dose for an extended time period while minimizing systemic distribution of toxic drug. Despite the upsurge of interest in focal targeted drug delivery, there is currently no single reference text on this subject.  Thus, the aim of the proposed book "Focal Controlled Drug Delivery" is to bring together leading experts and researchers in this field to provide an authoritative account of the essential pharmaceutical, technological, physiological and biological sciences underpinning the topic.  This book contains two sections- first section includes fundamental introductory chapters for focal drug delivery whereas, second section includes chapters describing drug delivery to body sites/system. The book allows clinical, pharmaceutical and biological scientists to offer their own perspectives on the subject, making it of potential interest to a wider audience than just drug delivery scientists. ABRAHAM J. DOMB is Professor for Medicinal Chemistry and Biopolymers at the Faculty of Medicine of the Hebrew University, Jerusalem, Israel. He earned Bachelor's degrees in Chemistry, Pharmacy and Law studies and PhD degree in Chemistry from Hebrew University. He did his postdoctoral training at MIT and Harvard Univ. USA and was R&D manager at Nova Pharm. Co. Baltimore USA during 1988-1992. During 2007-2012 he headed the Division of Identification and Forensic Sciences of the Israel Police. His primary research interests are in biopolymers, controlled drug delivery, cancer therapy, nanoparticulate systems, and forensic sciences. WAHID KHAN obtained his Master's and PhD in Pharmaceutics at the National Institute of Pharmaceutical & Educational Research (NIPER) Mohali India and worked with Prof. Abraham J. Domb in The Hebrew University of Jerusalem, Israel for his post doctoral research. Currently, he is working as Assistant Professor in Department of Pharmaceutics, NIPER, Hyderabad, India. He is having experience of working in areas of drug delivery, drug targeting, nanomedicine and biodesign of implantable medical devices. Dr. Khan has also won various national and international awards and fellowships including- Israel government prestigious PBC fellowships for outstanding Post-doctoral Researcher, Valazzi-Pikovsky and Lady Davis fellowship award.